Privilegi librari nell'Italia del Rinascimento - Squassina, Erika; Ottone, Andrea (Studi e ricerche di storia dell'editoria, 2019)
This work provides an in-depth description of the juridical framework in which the Italian book trade operated during the Renaissance. It is a multi-authored work that discusses issues related to intellectual, literary and artistic proto-property by taking into account some of the main urban centers of pre-unitary Italy such as Venice, Milan and Rome. It investigates the different legal systems put in place by the states and the dynamics that generated around them. The volume frames the topic at task within the general discourse on technologic innovation and state patronage in economic history hence exploring patenting systems (e.g., Florence and Venice) along with book privilege systems (e.g., Milan and Venice). In so doing it also investigates instances of conflicting interests occuring between the political and the economic sphere (e.g., Rome and Venice).